PERANCANGAN SISTEM INFORMASI MANAJEMEN ALAT BERAT BERBASIS WEB DI PT ROFENNI PRIMAJAYA - Darren Yang; Saut Pintubipar Saragih (LPPM Universitas Putera Batam, 2025)
In the digital era, information systems play an important role in improving operational efficiency, accelerating the decision-making process, and providing competitive advantages for organizations. PT. Rofenni Primajaya, which is engaged in the construction and heavy equipment rental sector, faces challenges in managing and monitoring the availability of heavy equipment, which is still done manually and takes a long time. The process of recapitulating the availability of heavy equipment using lobo reports and manual recording often takes 10 to 60 minutes, with the risk of errors that cause information on the availability of heavy equipment goods to not be provided quickly. In addition, there are errors in creating invoices caused by typing errors by administrative employees when using Microsoft Excel. Therefore, this study aims to design a web-based information system that is able to provide information on the availability of heavy equipment quickly and create invoices automatically. This study uses a system design method using UML and a system interface design method, namely Design Thinking.